Rebuilding Community after Katrina : Transformative Education in the New Orleans Planning Initiative - Forester, John, 1948-; Reardon, Ken, 1953- (Book collections on Project MUSE., 2016)
"Chronicles the innovative and ambitious partnership between Cornell University's City and Regional Planning department and ACORN Housing, an affiliate of what was the nation's largest low-income community organization. These unlikely allies came together to begin to rebuild devastated neighborhoods in New Orleans after Hurricane Katrina ... presents insights on the challenges involved in changing the way politicians and analysts imagined the future of New Orleans' Ninth Ward. What emerges from this complex drama are lessons about community planning, organizational relationships, and team building across multi-cultural lines."--Publisher description.